Entretien avec Gerardo Gandini : « Dans l’Argentine d’aujourd’hui, la composition est devenue une chose solitaire » - Sottile, Antonieta (Circuit, 2007)
Gerardo Gandini is one of the most influential composers in Argentina. Immersed in the hard social reality of Argentina, Gandini speaks in this interview of his conception of composition. As a result of the total absence of cultural policies on the part of the State, and the indifference of private sponsors and the media, the work of the composer takes place, according to Gandini, in painful isolation. Gandini also takes an original look at the power politics in the contemporary music world. Finally, Gerardo Gandini speaks of his experiences in the field of popular music, notably in collaboration with Astor Piazzolla.